Stability and recrystallization of amorphous solid dispersions prepared by hot-melt extrusion and spray drying - Martynek, Dominik; Ridvan, Luděk; Sivén, Mia; Šoóš, Miroslav (International journal of pharmaceutics, 2025)
Spray drying and hot-melt extrusion are among the most prevalent preparation techniques used in the pharmaceutical industry to produce amorphous solid dispersions (ASDs). This study advances previous research by integrating sample production, comprehensive analytical characterization, intrinsic dissolution rate measurements, and assessments of the behavior of ASDs under elevated temperature and humidity conditions. The study focuses on indomethacin, a widely used model for poorly soluble drugs, processed with PVP K30 or HPMC E5, both commonly used polymers. The findings demonstrate that hot-melt extruded samples exhibit superior stability against recrystallization, whereas spray dried samples achieve higher intrinsic dissolution rates. Furthermore, PVP K30 significantly outperforms HPMC E5 in the co-processing of indomethacin, enhancing both the intrinsic dissolution rate and the stability.
Keywords: farmaceutická chemie; stabilita léku; Hot Melt Extrusion Technology; Povidone; krystalizace; Humidity; Dissolution; vysoká teplota; pyrrolidiny; Spray Drying; Amorphous solid dispersions; indomethacin; Hot Temperature; Desiccation; vlhkost; sprejové sušení; Stability; Indomethacin; Chemistry, Pharmaceutical; Pyrrolidines; povidon; Spray drying; Solubility; Drug Liberation; Drug Stability; rozpustnost; Hot-melt extrusion; příprava léků; technologie extruze tavenin; methylcelulosa; Recrystallization; Methylcellulose; vysoušení; Crystallization; Drug Compounding; uvolňování léčiv